2015
DOI: 10.1177/1077699015581804
|View full text |Cite
|
Sign up to set email alerts
|

Co-Viewing Effects of Ethnic-Oriented Programming

Abstract: Entertainment consumption is often shared with others, whether friends or strangers. Whereas most co-viewing scholarship has examined parent-child viewing, few have examined viewing among in-group and out-group members. The present study explores in-group and out-group responses to racial comedy featuring disparaging information about the in-group. Findings suggest that Blacks report a more positive attitude, greater perceived similarity, and identification when viewing racially charged comedy with Black in-gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Thus, sitting with outgroup members and watching TV is not enough for reducing prejudice. Indeed, in two recent studies in which majority group members watched TV in the company of minority group members, there was no effect with regard to identifying with outgroup characters (Banjo et al, 2015) or perceptions of the outgroup as a whole (Schmader, Block, & Lickel, 2015). Both of these studies used comedy films as their stimulus, focusing on minority groups and using ethnic stereotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, sitting with outgroup members and watching TV is not enough for reducing prejudice. Indeed, in two recent studies in which majority group members watched TV in the company of minority group members, there was no effect with regard to identifying with outgroup characters (Banjo et al, 2015) or perceptions of the outgroup as a whole (Schmader, Block, & Lickel, 2015). Both of these studies used comedy films as their stimulus, focusing on minority groups and using ethnic stereotypes.…”
Section: Discussionmentioning
confidence: 99%
“…This prediction is in line with recent findings from research on coviewing that documents that who we watch with affects our identification with the characters on the screen. Banjo et al (2015) demonstrated that Black viewers identified more with a Black protagonist when they viewed a Black-oriented comedy with Black coviewers (compared with White coviewers). Similarly, participants identified more with a male protagonist depicted in an action movie when watching with a male coviewer than with a female coviewer (Tal-Or, 2016).…”
Section: The Interactive Effects Of Movie Type and The Coviewer's Ethmentioning
confidence: 98%
“…After watching the animation, children were given paper copies of questionnaires including demographic information (age, sex, race), Narrative Engagement (NE), Wishful Identification (WI), Physical Activity Intention (PAI), Social Desirability (SD), and the Multigroup Ethnic Identity Measures (MEIM). To minimize the potential co-viewing effect in interracial settings ( Banjo et al, 2015 ), RAs were assigned to match the majority of children’s racial backgrounds in each setting and remained neutral and stayed aside while operating the TVs. After they had completed the questionnaires, each participant received a $25 gift card.…”
Section: Methodsmentioning
confidence: 99%
“…The ethnicity of one’s co-viewer can also affect identification with media characters. In a recent study by Banjo, Appiah, Wang, Brown, and Walther (2015), African Americans who watched a comedy aimed at African Americans in the company of two in-group members identified more with its protagonists than those who watched with European Americans. The authors contended that minority groups are threatened by the way their group is perceived by the majority group when co-viewing a program that portrays racial stereotypes together with majority group members.…”
Section: The Effect Of Co-viewing On Identificationmentioning
confidence: 98%
“…With regard to the salience of ethnic identity, the situation is more complex. According to the distinctiveness theory, ethnic identity is more salient for minority groups (e.g., Banjo et al, 2015). Indeed, research has established that African Americans and Hispanic school children in the United States tend to mention their ethnicity as part of their self-description much more than Whites do.…”
Section: The Effect Of the Number Of In-group And Out-group Members’ mentioning
confidence: 99%